The Skills of Students of Psychology in Working with Psycho-Diagnostic Methods - A.I., Rasulov; M.A., Ibragimov (RA Journal of Applied Research, 2021)
In the psycho-diagnostics of the individual, it is important for specialists to be able to select research methods, provide their psychometric criteria, know the stages of compiling and adapting questionnaires, apply them and interpret empirical indicators. Such skills are provided at the stage of professional preparation of students majoring in psychology. The article analyzes the results of the empirical study of the professional competencies of students majoring in psychology to prepare them for the application of methods of psycho-diagnostics in research, to ensure their compliance with the criteria of psychometry. Psycho-diagnostic methods of students majoring in psychology; in particular, a multi-stage study has been established in the empirical study of the skills of applying personality questionnaires in psychological research. Empirical indicators cover the factors influencing the formation of students’ theoretical knowledge and practical skills in working with personal questionnaires, the ability to use questionnaires. Students’ theoretical knowledge and practical skills in working with personal questionnaires were analyzed over the academic years. Criteria such as the educational process, independent study of educational and scientific literature, professional motivation, the importance of having the ability to work with questionnaires, meeting the requirements of a science teacher are highlighted as factors influencing the formation of students’ skills in using personal handouts. Significance levels of empirical indicators obtained from the study were provided by mathematical-statistical methods.